2007
DOI: 10.1097/ta.0b013e31815bd78d
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study and Comparison of Magnetic Resonance Angiography (MRA) and Angiography Diagnosis of Blunt Vertebral Artery Injury

Abstract: 2D TOF MRA is an effective detection method of blunt vertebral artery injury but it might not be able to differentiate spasm, a small disruption of intima, from others under certain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Friedman et al [8] first described magnetic resonance angiography (MRA) as an imaging modality to detect vertebral artery injuries. Ren et al [12] confirmed the accuracy of MRA but noted it may lack the ability to identify small intimal tears. More recently, computed tomography angiography (CTA) has been shown to be a highly sensitive and specific modality for diagnosis of vertebral artery pathology in the setting of acute cervical spine trauma as well as chronic vertebral artery pathology [13][14][15].…”
Section: Historical Reviewmentioning
confidence: 99%
“…Friedman et al [8] first described magnetic resonance angiography (MRA) as an imaging modality to detect vertebral artery injuries. Ren et al [12] confirmed the accuracy of MRA but noted it may lack the ability to identify small intimal tears. More recently, computed tomography angiography (CTA) has been shown to be a highly sensitive and specific modality for diagnosis of vertebral artery pathology in the setting of acute cervical spine trauma as well as chronic vertebral artery pathology [13][14][15].…”
Section: Historical Reviewmentioning
confidence: 99%
“…Other imaging examinations such as ultrasound, MRI, conventional angiography or DSA have some defections or shortcomings; they cannot show both CJVA and C 0-1-2 on an image [12][13][14]. 3DCTA can clearly and directly show not only the anatomy and variations of VA but also its wall calcification and other pathological changes.…”
Section: Application Of Imaging Anatomymentioning
confidence: 99%
“…DSA can reveal the alterations of intimal consistency and remains the gold standard of detecting VAI but CTA has demonstrated adequate screening and follow-up accuracy, cost and time effectiveness and similar patient outcomes [1,2,[8][9][10]23]. CTA can also be more easily incorporated to emergency room protocols [24], while MRA constitutes a non-invasive and non-ionizing alternative, that has been found in animal models comparable to DSA as a modality of imaging for VAI [25].…”
Section: Discussionmentioning
confidence: 99%